Hope or despair: perceptions of punishment in accounts of incarcerated perpetrators of violent crimes in South Africa - Taitz, Jaimee (My University, 2022)
Physical punishment has been shown to influence a child’s later risk for perpetrating violence. However, there is very little research on how interpretations of the uses of punishment by caregivers feature in perpetrators’ narrative accounts of violent offending. Informed by a psychosocial approach and drawing on a deductive interpretivist thematic analysis of an existing corpus of transcribed interviews with violent offenders, this study explored the ways in which ten perpetrators of violent crime narrated the meanings of childhood punishment in their offending as adults. The analysis was undergirded by Winnicottian psychoanalytic conceptual thinking about management of the antisocial tendency, while paying attention to the social circumstances that drive physical punishment and that shape the moral logic of violence in the perpetrators’ development. My analysis demonstrates that in the participants’ formative years, the antisocial tendency and unconscious communication of hope was mismanaged by their caregivers. Primary caregivers, fathers, and teachers failed to provide a good-enough environment to withstand these behaviours and to understand their unconscious needs. As a result, violence and criminality become the only hope for these individuals to gain comfort, status, wealth, and satisfaction of needs. Additionally, these turns to violence become the only hope for individuals to gain the environmental provisions that were absent in their childhood. Informed by this analysis, the report suggests several early interventions that could facilitate caregivers to provide a good-enough environment for children in their care, while accounting for the stressors and difficulties that are present in their immediate environments. This could form one arm in an overarching strategy to prevent young children from becoming violent criminals through offering hope to developing children in South Africa.
Submitted in accordance with the partial requirements for the degree of Masters in Clinical Psychology in the Faculty of Humanities at the University of Witwatersrand, 2021